1994
DOI: 10.3109/07420529409057246
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Renal Hemodynamics in Unanesthetized, Unrestrained Rats

Abstract: Catheters were placed in the jugular vein and femoral artery of male Sprague-Dawley rats and connected to a specially designed perfusor for continuous constant infusion of 0.9% NaCl and a syringe to perform simultaneous and intermittent blood collections. This permitted continuous 24-h study of renal hemodynamics, estimated by inulin (Cin) and p-amino-hippuric acid (CPAH) clearances; Cin represents glomerular filtration rate and CPAH renal plasma flow. Animals were individually housed in metabolism cages in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Furthermore, bladder filling rate, and thus LUT output, depends upon the rate of urine production by the kidney. The diurnal variation in voiding frequency and volume reflects diurnal variation in glomerular filtration rate, bladder capacity, and autonomic function . Thus, many other factors contribute to voiding that were not assessed directly in the present study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, bladder filling rate, and thus LUT output, depends upon the rate of urine production by the kidney. The diurnal variation in voiding frequency and volume reflects diurnal variation in glomerular filtration rate, bladder capacity, and autonomic function . Thus, many other factors contribute to voiding that were not assessed directly in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…The diurnal variation in voiding frequency and volume reflects diurnal variation in glomerular filtration rate, bladder capacity, and autonomic function. 11,15,16 Thus, many other factors contribute to voiding that were not assessed directly in the present study. The strength of the relationship between void size and inter-void interval likely reflects the contribution of a number of these factors, including: the rate of production of urine (reflecting in large part glomerular filtration rate), which dictates how fast the bladder fills; bladder compliance (influenced by tissue biomechanics and autonomic tone) which affects bladder capacity; and the sensitivity of afferent and central pathways involved in transduction, transmission and integration of sensory information that contribute to setting the threshold for reflex control of bladder activity.…”
Section: Discussionmentioning
confidence: 92%
“…Drug excretion is influenced by kidney functions such as renal blood flow, glomerular filtration rate, and urine volume. Renal blood flow exhibits a significant circadian rhythm: it shows a peak during the active phase, which is twice the level of the peak seen during the resting phase in human and rats (40,41). Circadian oscillations in glomerular filtration rate are apparently synchronized with those of renal blood flow and systemic hemodynamics, with a 50% change at the day-night transition (42).…”
Section: Pharmacokineticsmentioning
confidence: 86%
“…They are active during the night and rest during the day, which is the opposite to humans. So diurnal rhythms of renal function in rats are reversed, that is, the peak of urinary electrolyte excretion occurs during the night‐time, and the peak of GFR and RBF occurs in active dark period (00.30 hours) …”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in rats have indicated that the peak of urinary electrolyte excretion occurs at night, and glomerular filtration rate (GFR) and renal blood flow (RBF) reached a peak in active dark period (00.30 hours). [6][7][8] Previously, diurnal rhythms of renal function were thought to be caused by external factors such as dietary intake, posture, or sleep; but they have been shown to persist over long periods of time under experimental conditions in which external factors were kept constant or were manipulated in a noncircadian manner. 9 These findings indicate that in addition to the external circadian stimuli (hormones, food, food metabolites) the functional rhythms are also controlled by a self-sustained intrinsic renal clock.…”
mentioning
confidence: 99%